2005
DOI: 10.1111/j.1600-0463.2005.apm1130107.x
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Legionella pneumophila colonization of a hospital water supply: efficacy of control methods and a molecular epidemiological analysis

Abstract: After a nosocomial outbreak caused by Legionella pneumophila serogroup 5, the hospital water distribution system, which was found to be colonized by L. pneumophila serogroups 5 and 6, was decontaminated by the superheat and flush method and by installing an additional heat-shock unit in one of the hot water circuits. This unit exposed the recirculated water to a temperature of 80 degrees C. The efficacy of the decontamination measures was evaluated by monitoring the temperatures and legionella concentrations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
29
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 19 publications
2
29
0
4
Order By: Relevance
“…The EWGLI database for L. pneumophila allele designations is particularly helpful in investigations of legionellosis cases in the hospital settings, as pointed out in recent reports (Ratcliff et al 1998;Amemura-Maekawa et al 2005;Perola et al 2005;Wong et al 2006;Ratzow et al 2007). Gene sequence-based phylogenic schemes are becoming widely used for microorganisms difficult to classify, as more sequences have been determined and sequencing methods have become simpler and more widely available.…”
Section: Discussionmentioning
confidence: 96%
“…The EWGLI database for L. pneumophila allele designations is particularly helpful in investigations of legionellosis cases in the hospital settings, as pointed out in recent reports (Ratcliff et al 1998;Amemura-Maekawa et al 2005;Perola et al 2005;Wong et al 2006;Ratzow et al 2007). Gene sequence-based phylogenic schemes are becoming widely used for microorganisms difficult to classify, as more sequences have been determined and sequencing methods have become simpler and more widely available.…”
Section: Discussionmentioning
confidence: 96%
“…However, isolated cases and outbreaks have been related to L. pneumophila sg5. In 2005, a nosocomial outbreak caused by L. pneumophila sg5 was reported in Finland [36]. In 2007, a case of nosocomial legionellosis due to L. pneumophila sg5 was reported in an Italian hospital whose WDS was contaminated by both L. pneumophila sg1 and sg5 and where nosocomial Legionella infections had never been previously detected [37].…”
Section: Discussionmentioning
confidence: 99%
“…RAPD analysis has been used mostly for intraspecies discrimination in epidemiological studies [1,2] . Our results showed that RAPD analysis is highly suited to differentiate between related and unrelated Legionella isolates and strains.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, discriminatory molecular typing methods should be applied to clinical and presumptively linked environmental strains in order to detect the source of infection. In this regard, random amplification of polymorphic DNA (RAPD)-PCR has been introduced as a reliable method to distinguish between phenotypically/serologically similar bacterial species and strains including legionellae [1,2] . In this study, RAPD-PCR was used for genotypic analysis of Legionella isolates from clinical and environmental sources.…”
mentioning
confidence: 99%